Digital Vernaculars: A Systematic Literature Review on Indonesian Gen Z Slang Across Social Media Platforms - Durahman, Eva Utami; Anwar, Aulia Arifbillah (Universitas Pahlawan Tuanku Tambusai, 2025)
Slang has emerged as a defining element of Indonesian Gen Z communication, particularly across social media platforms such as TikTok, Instagram, and WhatsApp. This linguistic trend reflects creativity, identity construction, and peer solidarity but also raises concerns over language change and the preservation of standard Indonesian. This study conducts a systematic literature review (SLR) to synthesize peer-reviewed research on Indonesian Gen Z slang, focusing on its types, characteristics, communication contexts, platform-specific patterns, and research gaps. Following PRISMA guidelines, searches were conducted in various databases including Semantic Scholar, PubMed, Google Scholar. Inclusion and exclusion criteria were applied, and eligible studies were analyzed thematically. The findings indicate that slang is formed through diverse morphological and phonological processes, including clipping, blending, and code-mixing with English (Indoglish), and that usage adapts to formality, audience, and platform culture. While qualitative methods dominate existing studies, research on regional variations, long-term educational impacts, and strategies to balance slang use with standard language remains limited. This review consolidates fragmented scholarship into a structured overview, providing a foundation for future research and offering insights for linguists, educators, and policymakers concerned with preserving linguistic heritage while embracing digital-era language innovation.